The Effect of Ambassador Fiki Naki's Brand on the Brand Image of Ruangguru - Feby Andarina; Berlian Primadani Satria Putri (Budapest International Research and Critics University, 2022)
Marketing communication that is commonly used is through advertising. One of the marketing communication strategies carried out by several companies or brands is a marketing strategy through brand ambassadors. Using a brand ambassador can cause an emotional appeal to the ad and this must be done in the right way such as choosing the right brand ambassador and also in accordance with the marketing target. The selection of brand ambassadors can be said to be the selection of brand speakers because according to Kotler and Armstrong (2018:163). One of the brand ambassadors used by Ruangguru is Fiki Naki, who is an influencer. Brand ambassadors are usually carried out by someone who has a wide network of scope and usually a brand ambassador will be chosen from the entertainment circle such as actors, models, athletes, and musicians to public figures who are respected by the community. (Appkey, 2020). This research was conducted to determine the effect of using Fiki Naki's brand ambassador on Ruangguru's brand image. This research uses the causal explanation quantitative research method. The sampling technique that will be applied is non-probability with the number of samples used as many as 400 respondents who are Ruangguru YouTube subscribers who know Fiki Naki. This test was carried out using the help of SPSS 26. Based on the results of the analysis in this study, the brand ambassador variable has an average score of 1535 or a percentage of 86.85%. The responses given by the respondents as a whole are included in the very good category. While the brand image variable has an average score of 1539 or a percentage of 77%. The responses given by the respondents as a whole are included in the good category. The calculated t value is 33,703 or greater than the t table, which is 1,966. The value of t table can be seen in the provisions of /2 = 0.05/2 = 0.025. The degree of freedom of the t table is dk= (400-(1+1)) = 389. So, it can be concluded that the value of t count > t table so that H0 is rejected and H1 is accepted. The results of the analysis of the coefficient of determination show that the R-Square value is 0.741 or 74.1%. Thus, the Brand Ambassador variable affects Ruangguru's Brand Image by 74.1%. While the rest is influenced by other variables not examined in this study.